2021
DOI: 10.1017/s0007114521000659
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and metabolic risk of neuropsychiatric disorders: insights from animal models

Abstract: Neuropsychiatric disorders are major causes of the global burden of diseases, frequently co-occurring with multiple comorbidities, especially obesity, type 2 diabetes mellitus, non-alcoholic fatty liver disease and its various risk factors in metabolic syndrome. While the determining factors of neuropsychiatric disorders are complex, recent studies have shown that there is a strong link between diet, metabolic state and neuropsychiatric disorders, including anxiety and depression. There is no doubt that rodent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 132 publications
0
7
0
Order By: Relevance
“…However, NAFLD constitutes a significant risk factor for cardiovascular disease (CVD), which is reported as the most common cause of mortality in this patient population ( 21 , 22 ). In parallel to the data highlighting NAFLD as an evolving epidemic, growing evidence also suggests direct associations between common mental health issues, such as depression, anxiety and chronic stress, and the metabolic syndrome ( 23 , 24 ). Based on the strong overlap between NAFLD and the metabolic syndrome, it seems likely that such associations may also be observed in individuals with NAFLD, potentially with shared underlying mechanisms that create a feed-forward vicious cycle between NAFLD and such mental health morbidity ( 12 ).…”
Section: Introductionmentioning
confidence: 94%
“…However, NAFLD constitutes a significant risk factor for cardiovascular disease (CVD), which is reported as the most common cause of mortality in this patient population ( 21 , 22 ). In parallel to the data highlighting NAFLD as an evolving epidemic, growing evidence also suggests direct associations between common mental health issues, such as depression, anxiety and chronic stress, and the metabolic syndrome ( 23 , 24 ). Based on the strong overlap between NAFLD and the metabolic syndrome, it seems likely that such associations may also be observed in individuals with NAFLD, potentially with shared underlying mechanisms that create a feed-forward vicious cycle between NAFLD and such mental health morbidity ( 12 ).…”
Section: Introductionmentioning
confidence: 94%
“…For the behavioural level, the current literature is filled with examples in which long-term exposure to high-energy diets alters cognitive performance and modulates emotionality [ 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. The latter can be defined as the measure of emotional behaviour related to undirected escape, avoidance of specific stimulus or area, immobility and sympathetic nervous system activation (e.g., heart rate, urination, defecation) [ 73 ].…”
Section: Important Considerations On the Use Of High-fat Diet Treatme...mentioning
confidence: 99%
“…The latter can be defined as the measure of emotional behaviour related to undirected escape, avoidance of specific stimulus or area, immobility and sympathetic nervous system activation (e.g., heart rate, urination, defecation) [ 73 ]. However, there are numerous discrepant findings, for instance in rodent models of depression [ 69 ]. The main theoretical premise behind the inconsistencies concerns variations in experimental designs (e.g., diet content and duration, exposure period; sex, age, species and genetic background of the animals used; behavioural tests).…”
Section: Important Considerations On the Use Of High-fat Diet Treatme...mentioning
confidence: 99%
“…In animal models, high-sugar or high-fat diets can induce depression-like behaviors, although variation in effects may exist depending on the species and genetic background of the animals used. Both C57BL/6 mice and rats have been frequently used to study mental disorders induced by high-fat diets, 14 and it has been reported that high-sugar diets may trigger depression-like behaviors in rats by altering HPA axis function and remodeling the transcriptomic alterations in the hypothalamus. 15 However, the effects of high-sugar diets on depression-like behaviors in mice are scarce and need further investigation.…”
Section: Introductionmentioning
confidence: 99%